STUDY OF THE EFFECT OF CHITOSAN HYDROXYAPATITE ON MORPHOLOGICAL INDICATORS OF RABBIT BLOOD (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
For the experiment, 16 heads of 1.5-2-month-old rabbits of local breed were taken from the ‘‘Flander Rabbits 1972’ LLC Farm, located in Mirzachul District, Jizzakh Region” M.Ch.J. The first group of rabbits was the control group and was fed with farm ration. 2-3 and 4 experimental groups were given 10 mg/kg of chitosan 20-80 to the second, 15 mg/kg to the third group, and 18 mg/kg of chitosan 70-30 to the fourth experimental group for 30 days. given during The effectiveness of the used drug was evaluated based on the morphological parameters of the blood.